(untitled) (Journal of Universal Science Research, 2024)
Cybercrime, a pervasive threat in our digital era, encompasses a range of illicit activities exploiting vulnerabilities in digital infrastructure. From financial fraud and identity theft to sophisticated cyber espionage and disruptive ransomware attacks, cybercriminals operate globally, impacting individuals, businesses, and governments alike. Addressing this multifaceted challenge requires robust cybersecurity measures, international cooperation, legislative frameworks, and public awareness campaigns to protect against evolving threats and safeguard digital ecosystems.